1984
DOI: 10.1063/1.447049
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and electron dynamics in the photodissociation of water

Abstract: The photodissociation of water in its first absorption band is studied by photolyzing H2O at 157 nm with an excimer laser. This dissociation proceeds directly to produce the electronic ground states of H and OH. Both nascent internal state distributions and alignment of the product OH (2Π) are probed by laser induced fluorescence. This is done with both warm (300 K) and cold (∼10 K) water. About 88% of the excess energy is translation, 10% vibration, about 2% rotation. The first three vibrational levels 0, 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(97 citation statements)
references
References 55 publications
6
90
1
Order By: Relevance
“…Indeed, several bands of the sequence ~v = 2 of OH were observed in the near-infrared spectrum of P/Halley . Laboratory measurements (Andresen et al 1984) have shown that the photodissociation of H20 at 157 nm yields more than 53% of OH in excited vibrational states, Assuming that the yield of v(l -0) OH emission subsequent to water dissociation is 50%, we infer an emission rate g = 6 x 10 -6 sec -1 per water molecule at 1 AU for this band, to be compared with g = 3.3 x 10 -4 sec I for the 2.7-p~m water bands in the optically thin case. Thus we expect an OH signal approximately one-fiftieth that of the water band (which is consistent with that observed by Tokunaga et al 1987), which can be seen against water emission in the IKS spectrum only with considerable difficulty.…”
Section: The Region 28-315 T~mmentioning
confidence: 99%
“…Indeed, several bands of the sequence ~v = 2 of OH were observed in the near-infrared spectrum of P/Halley . Laboratory measurements (Andresen et al 1984) have shown that the photodissociation of H20 at 157 nm yields more than 53% of OH in excited vibrational states, Assuming that the yield of v(l -0) OH emission subsequent to water dissociation is 50%, we infer an emission rate g = 6 x 10 -6 sec -1 per water molecule at 1 AU for this band, to be compared with g = 3.3 x 10 -4 sec I for the 2.7-p~m water bands in the optically thin case. Thus we expect an OH signal approximately one-fiftieth that of the water band (which is consistent with that observed by Tokunaga et al 1987), which can be seen against water emission in the IKS spectrum only with considerable difficulty.…”
Section: The Region 28-315 T~mmentioning
confidence: 99%
“…A significant fraction of the population in v 0 ¼ 1 of OH is expected to be a direct (vs. cascade) product of the parent's photolysis. For dissociation at 157 nm ( FAB), Andresen et al (1984) found that the population ratio for vibrational levels 0, 1, and 2 is 1:1: 0.15. In addition to direct production from H 2 O dissociation, some decay from higher vibrational levels to OH Ã (X 2 Å; v 0 ¼ 1) is also possible.…”
Section: The New Comet Data and Laboratory Studies Of H 2 O Photodissmentioning
confidence: 99%
“…Product OH Ã (X 2 Å ) distributions in different vibrational states have been measured in the laboratory, for water dissociation through both the first and the second absorption bands (hereafter referred to as FAB and SAB). In the FAB, the equivalent rotational temperatures of product OH Ã (X 2 Å ) vary from a few hundred to about 1000 K as the initial H 2 O rotational temperature is varied between $30 and $300 K (Andresen et al 1984;Häusler et al 1987). In the SAB, the OH Ã (X 2 Å) rotational distribution can be extremely ''hot,'' peaking at rotational quantum numbers N 0 $ 40Y45, equivalent to temperatures of tens of thousands of kelvin (Harich et al 2000).…”
Section: The New Comet Data and Laboratory Studies Of H 2 O Photodissmentioning
confidence: 99%
See 2 more Smart Citations